The impact of postpartum post-traumatic stress disorder symptoms on child development: a population-based, 2-year follow-up study. Issue 1 (29th September 2016) - Garthus-Niegel, S.; Ayers, S.; Martini, J.; von Soest, T.; Eberhard-Gran, M.
Abstract : Background: Against the background of very limited evidence, the present study aimed to prospectively examine the impact of maternal postpartum post-traumatic stress disorder (PTSD) symptoms on four important areas of child development, i.e. gross motor, fine motor, communication and social–emotional development. Method: This study is part of the large, population-based Akershus Birth Cohort. Data from the hospital's birth record as well as questionnaire data from 8 weeks and 2 years postpartum were used ( n = 1472). The domains of child development that were significantly correlated with PTSD symptoms were entered into regression analyses. Interaction analyses were run to test whether the influence of postpartum PTSD symptoms on child development was moderated by child sex or infant temperament. Results: Postpartum PTSD symptoms had a prospective relationship with poor child social–emotional development 2 years later. This relationship remained significant even when adjusting for confounders such as maternal depression and anxiety or infant temperament. Both child sex and infant temperament moderated the association between maternal PTSD symptoms and child social–emotional development, i.e. with increasing maternal PTSD symptom load, boys and children with a difficult temperament were shown to have comparatively higher levels of social–emotional problems. Conclusions: Examining four different domains of child development, we found a prospective impact of postpartum PTSD symptoms on children's social–emotional development at 2 years of age. Our findings suggest that both boys and children with an early difficult temperament may be particularly susceptible to the adverse impact of postpartum PTSD symptoms. Additional studies are needed to further investigate the mechanisms at work.